First record of host plant for Cogia stylites (Herrich-Schäffer, 1869) (Hesperiidae: Eudaminae) - Ayane Suênia-Bastos; Suianne Cajé; Jefferson Duarte-de-Mélo; Joshua Pablo Cavalcanti; Olaf Hermann Hendrik Mielke (Historia naturalis bulgarica, 2025)
This paper reports the butterfly Cogia stylites (Herrich-Schäffer, 1869) feeding on a Fabaceae tree species in Curitiba, Paraná, Brazil. The immature specimen was found inside its shelter, constructed using leaflets from the host plant identified as Senna multijuga subsp. lindleyana var. lindleyana (Gardner) H.S. Irwin and Barneby (Fabaceae: Caesalpinioideae). Other species of Cogia Butler, 1870, and the closely related genus Typhedanus Butler, 1870, have a specific relationship with plants of the genus Senna Mill. Thus, this is the first report of C. stylites feeding on Senna Mill. species.